MYCOREMEDIATION OF MONOCROTOPHOS - S.SAM MANOHAR DAS; S. ANITHA (International Journal of Pharma and Bio Sciences, 2011)
The persistence of Monocrotophos (MCP) an extensively used Organophosphorous pesticide in environment and its toxic effect on biota necessitate its removal. A soil fungus capable of utilizing or breaking down MCP was isolated from a site contaminated by the same pesticide. The fungus Aspergillus sp. was inoculated into the medium with 0.5% MCP. After 8 days of incubation the biodegradation of MCP was analyzed using GC-MS .The results of GC-MS revealed that the MCP got degraded into volatile fatty acids like Behenic acid,Stearic acid,Palmitic acid and other intermediate metabolites which were not found in the control medium. The finding of this study highlights the potential of Aspergillus sp. in the breakdown of MCP